Isothermal Remanent Magnetization (IRM) acquisition curves for petrologically representative IRD particles of sediment core GeoB18530-1 - Bukar, Shettima; von Dobeneck, Tilo; Hilgenfeldt, Christian (In: von Dobeneck, Tilo; Bukar, Shettima (2025): Rock magnetic, geochemical and sedimentological properties related to IRD composition and content of sediment core GeoB18530-1 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971785, 2025)
IRM acquisition curves (and their derivatives) resolve the cumulative coercivity distribution (and spectrum) of a magnetic mineral assemblage. Here we present data of larger, petrologically representative IRD particles of all observed lithologies. These IRM acquisition curves were acquired in logarithmically increasing pulse field steps from 10 mT to 2600 mT and measured by DC SQUIDS inside the 2G rock magnetometer without exposure to the external geomagnetic field. The varying magnetic peak field values shown here are based on real time peak field measurements by an integrated induction coil. Although samples were previously AF demagnetized, some samples have hard initial remanent magnetizations that were not entirely removed.
Keywords: Geochemistry; grain size distribution; Grand Banks Margin; Heinrich events; Ice-Rafted Detritus; rock magnetism